Slovak Republic : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This Selected Issues paper examines the need of reformation of the Fiscal Responsibility Act (FRA) in the Slovakia. It is suggested that in light of experience gathered so far, FRA modifications should be considered. Clear guidelines regarding a cost-effective cash management strategy should be established. Debt brake level should be kept at the current limits, rather than lowered over time, to avoid unduly eroding fiscal space. Policies should aim to maintain a safe margin below debt thresholds to allow fiscal policy to play a counter-cyclical role in the future during downturns. Adjustment measures should be more gradual and the bias toward spending cuts should be lessened or removed.